The effect of using (Swom) strategy in learning the effectiveness of the payment of gravity for intermediate students - Taha, Hydar (Journal of Physical Education, 2014)
The research aims to identify the impact of the use of strategy Som (Swom) in learning the effectiveness of the payment of gravity of the intermediate stage, The sample consisted of a number of graders Aalthani average in the medium consistency for Boys and totaling 45 students, has been divided the sample into two groups randomly , (23) students of the experimental group, and (22) a student of the control group were applied tutorial on the experimental group, the researcher used the test the skill of the effectiveness of, and after giving the scheduled program was conducted post-test, and after receiving the results have been arranged in tables and subjected to treatments statistical, has concluded that the most important include the following (1 - helped strategy som (swom) learner to be positive in thecollection of information, organization, and follow-up, straightened during the learning process, which has helped in learning the effectiveness of the payment of gravity better than the control group) and the most important recommendations include adoption of a strategy som (swom) when learning the effectiveness of pay heavyweight phase average